Pengembangan Bahan Ajar Al-Qur’an Hadits Berbasis Digital dalam Meningkatkan Minat Belajar Siswa - Athiyyaturrahmah, Athiyyaturrahmah; Zainab, Nurul (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose - This study aims to create digital-based instructional materials for the Qur'an and Hadith and assess their impact on students' learning interests. Typically, Quran and Hadith classes are perceived as monotonous due to the limited involvement in the predominantly teacher-centered learning process. Consequently, students' enthusiasm for learning tends to diminish. Therefore, the development of instructional materials is pursued for this specific purpose. The research was conducted at MTs AL-Amien Jambu Lenteng Sumenep, focusing on 8th-grade students as the research subjects.Methods - The type of research is Research and Development (R&D) using the ADDIE model: analysis, Design, Development, Implementation, and evaluation. Findings - The research reveals that developing digital-based teaching materials for the Quran and Hadith involves analyzing instructional needs, and designing, developing, and evaluating the materials. Canva and Flipbook applications were used in the development, resulting in E-Book format materials. Expert validation yielded an 85% validation rate, with material experts providing an 87.5% validation rate. The average validity, combining both validators, was 86.94%. Following this, a trial was conducted, and students evaluated the materials through a questionnaire, achieving an 88.33% satisfaction rate.Research Implications - Based on these findings, the development of digital-based teaching materials for the subjects of Quran and Hadith has proven to be highly beneficial in enhancing the learning interest of 8th-grade students at MTs Al Amien Jambu. The implication is that students are enthusiastic about learning and highly engaged in the learning process, leading to the achievement of learning objectives.